Advantage of extracellular vesicles in hindering the CD47 signal for cancer immunotherapy - KIM YOON KYOUNG; Yeonsun Hong; Bae Young Rang; Goo, ji young; Seong A KIM; YunjungChoi; Gi-hoon Nam; Minsu Kwon; Seung Gyu Yun; LEE GYEJUN; Jeong, Cherlhyun; Kim, In San (Elsevier BV, 2022)
The cluster of differentiation 47 (CD47) protein is abundantly expressed on various malignant cells and sup-presses the phagocytic function of macrophages and dendritic cells. High CD47 expression levels are correlated with poor cancer survival. Antagonizing CD47 antibodies with potent antitumor effects have been developed in clinical trials, but have critical side effects, inducing anemia and thrombocytopenia. To develop a safe and potent CD47 blockade, we designed extracellular vesicles (EVs) harboring signal regulatory protein alpha (SIPR alpha)-EV-SIRP alpha (EVs that express SIPR alpha). EV-SIRP alpha showed minimal toxic effects on hematologic parameters and utilized RBCs as delivery vehicles to tumors rather than inducing anemia. EV-SIRP alpha inhibited ligation of residual CD47 molecules, which attribute to the EV-endocytosis-mediated CD47 depletion and steric hindrance of EV. In an immunologically cold tumor model, EV-SIRP alpha induced tumor-specific T-cell-mediated antitumor effects. When directly administered to the accessible lesions, EV-SIRP alpha monotherapy elicited an abscopal effect in the B16F10 tumor model by increasing immune cell infiltration and CD8(+)-mediated immunity against non-treated tumors. The combinational approach by loading doxorubicin into the EV-SIRP alpha dramatically reduced the tumor burden and led to 80% complete remission rate. Thus, a potent EV-based CD47 blockade that is hematologically safe, has efficient signaling blocking efficacy, and has systemic antitumor immunity against cancer is recommended.